Esophagus cancer and essential trace elements - Yang, Xin; Tang, Zhe; Li, Jing; Jiang, Jizong (Frontiers in Public Health, 2022)
Numerous epidemiological and laboratory studies on essential trace elements have reported protective association in the development of various cancer types including esophagus cancer (EC). However, the results are not always consistent. Some essential trace elements could play a vital role in preventing esophagus cancer, some showed no association with esophagus cancer risk, while some even do harm to individuals. This article reviews the association between the intake or supplementation of essential trace elements (especially zinc, copper, iron, selenium) and the risk of esophageal cancer. Generally, Zinc intake may decrease the risk of esophageal cancer (EC), especially in high esophageal squamous cell carcinoma (ESCC) prevalence regions. The association between copper supplementation and EC remains uncertain. For iron, it was widely accepted that total iron intake may be related with reduced EC risk while heme iron intake may be related with increased EC risk. Selenium intake showed a protective effect against EC, especially for those individuals with a low baseline selenium level. This review also prospects the research direction of the association between EC and essential trace elements.